Evaluating Tuberculosis and Drug Resistance in Serbia: A Ten-Year Experience from a Tertiary Center - Mihailo Stjepanovic; Snjezana Mijatovic; Nikola Nikolic; Nikola Maric; Goran Stevanovic; Ivan Soldatovic; Aleksandra Barac (Antibiotics)
Background: Tuberculosis (TB) remains a leading cause of mortality worldwide, particularly in low- and middle-income countries. The rise of multidrug-resistant TB (MDR-TB) poses significant challenges to global health. This study reviews the experience of the largest pulmonology center in Serbia, a country with low MDR-TB incidence, focusing on TB prevalence, resistance detection, and treatment strategies between 2012 and 2021. Methods: We retrospectively analyzed a total of 1239 patients who were diagnosed and treated for TB in the period from 2012 to 2021 at University Clinical Center of Serbia. Results: Drug resistance was identified in 21 patients (1.7%), with the highest resistance to rifampicin (1.4%) and isoniazid (1.3%). Pyrazinamide and streptomycin resistance were detected in only a few cases. Patients with resistant TB were younger on average, though the difference was not statistically significant (46.4 ± 19.1 vs. 53.6 ± 18.4, p = 0.079). Prior TB history was more frequent in the resistant group, almost reaching statistical significance (4 vs. 82, p = 0.052). Conclusions: These findings underscore the critical importance of sustained surveillance, particularly of latent and drug-resistant TB forms, in alignment with the World Health Organization’s (WHO) TB control strategy to preserve Serbia’s low-incidence status. Moreover, given Serbia’s strategic location on a major migration route, there is an elevated risk of new TB cases emerging and potential shifts in TB-drug-resistance patterns developing in the future.